Mineralocorticoid receptor antagonism induces browning of white adipose tissue through impairment of autophagy and prevents adipocyte dysfunction in high‐fat‐diet‐fed mice. Issue 8 (7th May 2014) - Armani, Andrea; Cinti, Francesca; Marzolla, Vincenzo; Morgan, James; Cranston, Greg A.; Antelmi, Antonella; Carpinelli, Giulia; Canese, Rossella; Pagotto, Uberto; Quarta, Carmelo; Malorni, Walter; Matarrese, Paola; et al.
Abstract : The mineralocorticoid receptor (MR) controls adipocyte function, but its role in the conversion of white adipose tissue (WAT) into thermogenic fat has not been elucidated. We investigated responses to the MR antagonists spironolactone (spiro; 20 mg/kg/d) and drospirenone (DRSP; 6 mg/kg/d) in C57BL/6 mice fed a high‐fat (HF) diet for 90 d. DRSP and spiro curbed HF diet‐induced impairment in glucose tolerance, and prevented body weight gain and white fat expansion. Notably, either MR antagonist induced up‐regulation of brown adipocyte‐specific transcripts and markedly increased protein levels of uncoupling protein 1 (UCP1) in visceral and inguinal fat depots when compared with the HF diet group. Positron emission tomography and magnetic resonance spectroscopy confirmed acquisition of brown fat features in WAT. Interestingly, MR antagonists markedly reduced the autophagic rate both in murine preadipocytes in vitro (10 ‐5 M) and in WAT depots in vivo, with a concomitant increase in UCP1 protein expression. Moreover, the autophagy repressor bafilomycin A1 (10 ‐8 M) mimicked the effect of MR antagonists, increasing UCP1 protein expression in primary preadipocytes. Hence, we showed that adipocyte MR regulates brown remodeling of WAT through a modulation of autophagy. These results provide a rationale for the use of MR antagonists to prevent the adverse metabolic consequences of adipocyte dysfunction.—Armani, A., Cinti, F., Marzolla, V., Morgan, J., Cranston, G. A., Antelmi, A., Carpinelli, G., Canese, R., Pagotto, U., Quarta, C., Malorni, W., Matarrese, P., Marconi, M., Fabbri, A., Rosano, G., Cinti, S., Young, M. J., Caprio, M. Mineralocorticoid receptor antagonism induces browning of white adipose tissue through impairment of autophagy and prevents adipocyte dysfunction in high‐fat‐diet‐fed mice. FASEB J. 28, 3745–3757 (2014). www.fasebj.org